IMPROVING STUDENTSâ ENGLISH SPEAKING SKILL THROUGH PORTOFOLIO CONFERENCE (A Classroom Action Research at Politeknik Madiun) - Mulyani, Mulyani; Tarjana, Samiati; Tarjana, Heribertus (ENGLISH LANGUAGE TEACHING IN INDONESIA, 2014)
This study belongs to Classroom Action Research (CAR). This classroomaction research was conducted in Politeknik Madiun in the second semesteracademic year 2012 â 2013, during October to December period with 6 meetingsdivided into 2 cycles. The subyects of this research are the students of PoliteknikMadiun especially students in the second semester which consist of 37 students,they are 35 boys and 2 girls. Portfolio conference had changed the teaching and learning condition. Theteaching and learning condition has progressed positively in one meeting toothers. Eventhough the condition of the class changed from not conducive intoconducive, inactive into active, not alive into alive, uninteresting becameinteresting. The progress can also be seen from the improvement of the amount ofstudents who participated through the studentsâ presence, discussion, interaction,and performance in the speaking class.Key words : portofolio conference, speaking skill and data reduction